Control and analysis of a 3‐level diode‐clamped split source inverter in the applications of grid‐tied photovoltaic systems. (19th August 2020) - Nannam, Hari Charan; Babu, Chitti; Banerjee, Atanu
Abstract: Back ground and Aim: In this work, a new control scheme is developed to track the peak power from a solar energized grid‐tied three‐level diode‐clamped split source inverter (DCSSI). Material and method: Two isolated photovoltaic sources (PV) are considered as sources for the topology. The impedance network serves as a voltage booster and enhances the input PV voltage. Two individual perturb and observe maximum power tracking algorithms are used to pursue the peak power and to generate two individual dc‐link voltage references. A new dc‐link voltage reference is developed by the addition of the two individual voltage references. Results: The proposed control scheme is tested with different cases to investigate the optimum performance of the DCSSI. Primarily, the control scheme is examined with MATLAB/SIMULINK. To validate experimentally, a 5KVA DCSSI prototype is designed along with two individual impedance networks. An SP‐110 pyranometer is used to sense the variable irradiance. A Spartan‐6 XC6SLX25 field programmable logic array (FPGA) is used to generate the control algorithm for the DCSSI. Conclusion: Simulation and experimental results demonstrate the robustness of the proposed control scheme. Abstract : The application of diode clamped split source inverter in the application of grid‐tied photovoltaic applications. A new MPPT control strategy is designed to track the peak power from the PV systems. Different case studied elucidates the robustness of the control scheme.